Electrodeposition of Graphitic Carbon Nitride and its In situ Decoration with MnO2 Nanostructures: A Tailored Interface for Dopamine Sensing - Singh A.K.; Keshari P.; Saroj A.; Ramanathan V.; Rosy (My University, 2025)
Graphitic carbon nitride (gCN), a polymeric metal-free semiconductor, can emerge as a potential recognition element, offering abundant electron-donor N-sites for chemical interactions with analytes. However, poor dispersibility, agglomeration, and impeded electron transfer are some challenges that hinder its efficient use in electrochemical systems. Herein we propose the electrodeposition of gCN and its in situ decoration with MnO2 nanostructures as a solution to impeded charge transfer and gCN surface agglomeration. To do so, step by step electrodeposition mechanistic of gCN, MnO2, and their composite is deciphered. The modified electrode's electrochemical response and surface functionalities has been investigated using in-depth surface, chemical, and electrochemical characterization. For practical applicability, gCN.MnO2 functionalized interface has been used for sensing Dopamine, one of the essential catecholamine neurotransmitters. Exhibiting a two-fold increase in the oxidation current, the tailored electrode demonstrates 22% more sensitivity compared to the unmodified electrode. The proposed sensor was able to selectively determine Dopamine with a limit of detection as low as 20 nM, clearly manifesting the synergistic role of gCN and MnO2 in facilitating the electrochemical oxidation of Dopamine. The obtained electrode endows a remarkable performance in assaying Dopamine in pharmaceutical and food samples with an error of < 3%. We believe this study proposes electrochemical surface functionalization as a promising strategy to tailor gCN for sensitive and selective electrochemical systems, which can further be used to engineer commercial electrodes like screen-printed electrodes. © 2023 Elsevier B.V.